The Price of Parity in the European Union: analysis of the regulatory evolution of price parity clauses and their impact - Cabello Chaure, María (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper examines the regulatory and jurisprudential developments regarding price parity clauses on digital hotel booking platforms in the European Union. In particular, it focuses on the impact of the recent regulation introduced by Regulation 2019/1150 (P2B), Regulation 2022/720 (VBER) and Regulation 2022/1925 on Digital Markets (DMA). From a legal and economic perspective, the impact of price parity clauses is assessed, highlighting their pro-competitive and anti-competitive effects. The study chronologically lists the most relevant regulatory responses and court decisions in different Member States, including the judgment of the Court of Justice of the European Union in case C-264/23. Finally, recommendations are proposed to achieve more effective regulations capable of addressing the challenges of the digital hotel market. Particular emphasis is placed on the importance of algorithmic transparency and better coordination between the various European regulatory instruments.
Keywords: Price parity clauses; hotel booking platforms; OTAs; Booking.com